Highly distorted bipolar host material based on benzimidazole and indole derivative for efficient green and red solution-processed PhOLEDs. Issue 41 (8th October 2020) - Gao, Zhixiang; Yang, Tingting; Qu, Wenshan; Li, Jiangang; Fan, Xiaxia; Tian, Xiangbin; Li, Wei; Zhu, Hongwei; Huang, Jinhai; Dong, Lijuan; Shi, Yunlong; Wang, Hua
Graphical abstract: Highlights: A highly distorted benzimidazole and indole-based host material DY1 was developed. DY1 exhibited good thermal stability, high triplet energy and bipolar property. Solution-processed green and red PhOLEDs achieved high EQEs and low roll-offs. Abstract: A novel bipolar host material 2-(2′-(5-(dibenzo[ b, d ]furan-4-yl)- 1H -indol-1-yl)-[1, 1′-biphenyl]-3-yl)-1-phenyl- 1H -benzo[ d ]imidazole (DY1 ) based on electron-donating indole and electron-withdrawing benzimidazole was designed and synthesized for solution-processed phosphorescent organic light-emitting diodes (PhOLEDs). The highly distorted conformation derived from the orthogonally connected donor and acceptor on the 1, 3′-biphenyl bridge endowed DY1 with high thermal stability ( T g 122 °C) and a high triplet energy of 2.69 eV. Solution-processed PhOLEDs fabricated with DY1 host achieved excellent performance of 47.05 cd/A, 34.0 lm/W and 14.27% for green PhOLED, and 32.95 cd/A, 17.0 lm/W and 16.57% for the red PhOLED, respectively. This result revealed the structural advantage of the host material in high efficiency and low efficiency roll-off in PhOLEDs.